Comparing chamber and eddy covariance based net ecosystem CO2 exchange of fen soils. Issue 2 (15th March 2017) - Poyda, Arne; Reinsch, Thorsten; Skinner, R. Howard; Kluß, Christof; Loges, Ralf; Taube, Friedhelm
Abstract: Due to their high emission potential, the reporting of CO2 emissions from peatlands requires exact emission factors for different land use categories. Recently used emission factors are mainly based on CO2 flux measurements by chamber techniques or the micrometeorological eddy covariance (EC) method. However, evidence about the reliability and comparability of annual CO2 balances based on these methods is scarce. Therefore, manual chamber measurements of ecosystem respiration (RECO ) and net ecosystem exchange (NEE) were conducted for two years (March 2012–April 2014) to model annual balances of two sites on fen soils with different land use intensity in northern Germany: an unutilized and rewetted grassland (UG) and an intensively utilized wet grassland (GW). Simultaneously, EC measurements of NEE were conducted on the sites. Two reasons for occasionally great deviations in NEE between the methods could be observed: (1) the accordance of both methods was most hampered during transition periods such as the beginning of the growing season and the onset of regrowth after a grassland defoliation due to different spatial scales of EC and chamber measurements and (2) RECO and gross primary production (GPP) partitioned from EC NEE measurements were systematically lower than those from the chamber‐based model, which could be a result of the EC energy balance gap. Differences were more pronounced for the managed site GW as a result of more frequent regrowth periods. It is concluded that the EC and chamber method can show comparable results for the CO2 exchange of grasslands on fen soils when the limitations of both methods are known and considered for the reporting of emission factors. These limitations are due to energy balance closure and potentially biased footprints for EC and a restricted representativeness especially during early stages of plant development for the chamber method.